The study of inorganic absorber layers in perovskite solar cells: the influence of CdTe and CIGS incorporation - Montoya De Los Santos, I.; Courel, Maykel; Moreno-Oliva, Víctor Iván; Dueñas-Reyes, Efraín; Díaz-Cruz, Evelyn B.; Ojeda-Martínez, M.; M. Pérez, Laura; Laroze, David (Scientific reports, 2025)
The perovskite solar cell has been the subject of intense breakdown lately because of its exceptional efficiency. Nevertheless, they confront a significant challenge due to the absorber layer’s (perovskite) sensitivity to oxygen and water, which can cause rapid material degradation and adversely affect the solar cell’s performance. The commonly used organic hole transport layer (HTL), Spiro-OMeTAD, tends to degrade over time, exacerbating the issue. To address this challenge, two-stage research was conducted. Initially, the CH 3 NH 3 PbI 3 thin film was experimentally prepared, and XRD analysis confirmed the material’s satisfactory crystalline phase (tetragonal), with a crystal size of 73.9 nm. An energy band gap of 1.55 eV was obtained experimentally, demonstrating good correspondence with the literature. Then, perovskites with different crystal structures (cubic, tetragonal, and orthorhombic) were calculated by DFT. These calculations obtained energy band gaps with values of 1.5 eV for the cubic, 1.7 eV for the tetragonal, and 3.9 eV for the orthorhombic. Subsequently, a numerical simulation study using SCAPS was carried out to validate the theoretical performance of an experimental solar cell with Spiro-OMeTAD as the HTL. Also, a simulation without HTL was performed to highlight its importance. Finally, comparative studies were conducted to evaluate the feasibility of incorporating CdTe and CIGS as inorganic absorbing layers within perovskite solar cells (MAPI). The objective was to investigate their potential for cooperative behavior in light absorption and charge transport. The findings indicated that the CIGS absorbing layer outperformed both materials, achieving an efficiency of 15.67%. Furthermore, an optimization study for the CIGS layer was performed, resulting in enhanced output parameters, including a maximum efficiency of 28.32%. This research represents a significant advancement in developing stable and efficient perovskite solar cells.